Joint queue-perturbed and weakly coupled power control for Wireless Backbone Networks - Olwal, Thomas Otieno; Djouani, Karim; Kogeda, Okuthe P.; Wyk, Barend Jacobus van (Zielona Góra: Uniwersytet Zielonogórski)
Wireless Backbone Networks (WBNs) equipped with Multi-Radio Multi-Channel (MRMC) configurations do experience power control problems such as the inter-channel and co-channel interference, high energy consumption at multiple queues and unscalable network connectivity. Such network problems can be conveniently modelled using the theory of queue erturbation in the multiple queue systems and also as a weak coupling in a multiple channel wireless network.
Keywords: decentralized power control; singular perturbation theory; weak coupling theory; wireless backbone networks; optimal control theory